Tanggung Jawab Orang Tua Kepada Anak di Era Digital Perspektif Hukum Keluarga Islam di Indonesia - Nur Ahmad Yasin (AL-HUKAMA, 2018)
The digital age is an era where technology and information can be accessed by anyone, anywhere and under any conditions, so that it can have a positive and negative impact on parents’ responsibilities to children and child development. This article is the result of a bibliographical study on parents’ responsibilities to children in the digital age under the perspective of Islamic family law in Indonesia. Data are collected using documentation techniques and analyzed using descriptive methods with deductive mindset. Based on this study, parents are responsible for being more selective in nurturing, educating, and protecting children in today’s digital era. They are also asked to understand information technology and systems. Parents must be able to actualize children’s rights, including: maintenance of honor (?if? al-'ir?), maintenance of religious rights (?if? al-d?n), maintenance of the soul (?if? al-nafs), maintenance of reason (?if? al -'aql) and maintenance of property (?if? al-m?l).